2016
DOI: 10.5335/rfo.v21i2.6132
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do grau de conversão de resinas compostas fotoativadas em diferentes tempos e potências

Abstract: Introdução: uma polimerização adequada é crucial para a obtenção das propriedades físicas ideais e o desempenho clínico das resinas compostas. Objetivo: avaliar o grau de conversão (GC) e dureza de resinas IntroduçãoDesenvolvidas por Bowen durante a década de 1960, as resinas compostas à base de BisGMA passaram por transformações com o intuito de melhorar suas propriedades mecânicas e estéticas 1 . Concomitantemente à evolução desses materiais, os pacientes buscam cada vez mais a excelência estética ao sorrir,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…According to some authors, there is still no consensus on an ideal hardness value for composite resins. However, a study showed that, for composite resins, the value considered correct would be a hardness value greater than 50 VHN -Vickers hardness number [17]. Corroborating with these authors, this study showed that the resins studied here have acceptable surface hardness values.…”
Section: Resultssupporting
confidence: 68%
“…According to some authors, there is still no consensus on an ideal hardness value for composite resins. However, a study showed that, for composite resins, the value considered correct would be a hardness value greater than 50 VHN -Vickers hardness number [17]. Corroborating with these authors, this study showed that the resins studied here have acceptable surface hardness values.…”
Section: Resultssupporting
confidence: 68%
“…The photoinitiator and coinitiator are present in the composite resin. The photoinitiator absorbs light and interacts with the coinitiator, then, producing free radicals that are responsible for the polymerization process [7][8][9] . Camphorquinone is the most used photoinitiator, it has a maximum wavelength absorption at 470 nm 10 .…”
Section: Introductionmentioning
confidence: 99%